The impact of digitalization and Industry 4.0 on the audit - Hegedűs Mihály; Nedelka Erzsébet; Гегедюш М. (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola-"RIK-U" Kft., 2019)
Abstract. The phenomenon of globalization has a great impact on social and economic processes, and as its result, the world has accelerated, processes have been automatized, digitalization has become part of everyday life, and solutions using artificial intelligence are becoming more and more widespread nowadays. They help in continuous monitoring, assessment of risk and control, so the whole. audit activity. The generations react differently to the changes and opportunities offered by these changes. While the X generation has to learn the new technology, for Y generation it is just part of life from the birth and the Z generations simply cannot live without it. In our study, we have examined the impact of digitalization and digital processes on auditing, and attitudes related to them. We have compared generations’ point of views on new technologies and techniques, as well as how intergenerational co-operation affects them, and what they find the largest problem in accounting areas. As a conclusion, we found that the main problem is professional training and then the digital world, while intergenerational conflicts have come to the last place.

A globalizáció jelensége kihat a társadalmi és gazdasági folyamatokra egyaránt és ennek következtében a világ felgyorsult, a folyamatok automatizálódtak, a digitalizáció a mindennapi élet részévé vált, és a mesterséges intelligenciával működő megoldások alkalmazása egyre elterjedtebbé válnak. Ezek segítik a folyamatos ellenőrzést, a kockázat- és kontrollértékelést, tehát az audit tevékenységet. A változásokra és a változások nyújtotta lehetőségekre az egyes generációk másként reagálnak. Míg az X generációnak tanulnia kell, az Y generáció életének a kezdetektől fogva a része ez az új technológia, a Z generáció pedig már egyszerűen nem is tud élni nélküle. Tanulmányunkban a digitalizáció, a digitális folyamatok könyvvizsgálatra gyakorolt hatását vizsgáltuk, illetve az ezzel kapcsolatos attitűdöket. Összehasonlítottuk az egyes generációk véleményét az új technológiákkal, technikákkal kapcsolatban, illetve, hogy mennyire jelent számukra gondot a generációk közötti együttműködés, valamint mit találnak a legnagyobb problémának a számviteli területeken. Végső következtetésként megállapítottuk, hogy a legfőbb gondot a szakképzés jelenti, és ezt követően a digitális világ, míg a generációk közötti konfliktus az utolsó helyre került.
https://kmf.uz.ua/wp-content/uploads/2021/02/limes-2019_tom-vi_vi-evfolyam.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00008405
Keywords: auditing; simultaneity; digitization; control